Light at the end of the tunnel - Nash, George (Documenta Praehistorica, 2006)
This paper explores how megalithic art may have been viewed during a period when Neolithic monuments were in use as repositories for the dead. The group of monuments discussed are primarily passage graves which were being constructed within many of the core areas of Neoli- thic Atlantic Europe. Although dates for the construction of this tradition are sometimes early, the majority of monuments with megalithic art fall essentially within the Middle to Late Neolithic. The art, usually in the form of pecked abstract designs appears to be strategically placed within the inner part of the passage and the chamber. Given its position was this art restricted to an elite and was there a conscious decision to hide some art and make it exclusively for the dead? In order to discuss these points further, this chapter will study in depth the location and subjectivity of art that has been carved and pecked on three passage graves in Anglesey and NW England. I suggest that an encoded grammar was in operation when these and other passagegrave monuments with megalithic art were in use.
Keywords: zahodna Evropa; prazgodovina; arheološke najdbe; prazgodovinska umetnost; neolitik; grobnice; spomeniki; nagrobniki; kamen